AFRICAN COURT ON HUMAN AND PEOPLES' RIGHTS JURISDICTION IN PROSECUTING HUMAN RIGHTS VIOLATIONS BY RWANDA IN THE DEMOCRATIC REPUBLIC OF CONGO - Lintang Aulia Zahra; Davilla Prawidya Azaria (RADJA PUBLIKA, 2025)
This study investigates the jurisdictional capacity of the African Court on Human and Peoples' Rights (AfCHPR) in adjudicating transnational human rights violations, with a focus on the Democratic Republic of Congo’s (DRC) case against Rwanda concerning alleged support for the M23 rebel group. Drawing on normative legal methods and qualitative analysis, the paper examines the limitations of DRC's domestic judicial system in addressing grave human rights abuses, particularly in conflict zones marked by institutional fragility, corruption, and impunity. Despite legal reforms and ratification of major human rights instruments, the DRC remains unable or unwilling to ensure accountability for violations, especially those involving foreign actors. In response to these systemic shortcomings, the DRC has turned to the AfCHPR, marking a significant legal milestone as the first inter-state case before the Court. The paper explores the legal foundations for the AfCHPR’s jurisdiction under regional and international instruments, while also analysing Rwanda’s objections concerning admissibility and territorial competence. By assessing relevant case law, including Zongo v. Burkina Faso and Ogiek v. Kenya, the research highlights the AfCHPR's growing legitimacy as a regional mechanism for human rights enforcement. This case signals a broader shift toward accountability and justice in Africa, challenging traditional notions of sovereignty in favour of state responsibility and victim protection.